Effects of Non-Symbiotic Nitrogen Fixing Bacteria on Growth of Red Mangrove, Rhizophora mucronata Lam., Seedlings - Nimrat, Subuntith; Sonklin, Supannee; Vuthiphandchai, Verapong (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2020)
The purpose of this study was to investigate the effects of non-symbiotic nitrogen fixing bacteria on soil properties and growth of red mangrove (Rhizophora mucronata) seedlings. The experiment was divided into 4 treatments: 1) control (no bacterial inoculation), 2) addition of Bacillus sp. SN1, 3) addition of Bacillus sp. SN2, and 4) addition of a mixture of Bacillus sp. SN1+SN2+SN3. After planting seeds for 37 days, the addition of Bacillus sp. SN1, Bacillus sp. SN2 or mixed inoculum of Bacillus sp. SN1+SN2+SN3 significantly (P < 0.05) increased length and weight of seedlings. Additionally, the highest ammonium concentration was observed in Bacillus sp. SN1-treated soil (1.55±0.02 ppm), followed by soil treated with Bacillus sp. SN2 (0.93±0.008 ppm) and Bacillus sp. SN1+SN2+SN3 (0.45±0.000 ppm), respectively while no ammonium was detected in the control. Concentration of available phosphorus in Bacillus sp. SN2-treated soil was 1.04±0.110 ppm, which was significantly (P < 0.05) higher than that of the control (0.99±0.005 ppm). Addition of the three forms of nitrogen-fixing Bacillus had no effects on pH and organic matter in the soil. In conclusion, Bacillus sp. SN1, Bacillus sp. SN2 and a mixture of Bacillus sp. SN1+SN2+SN3 had the potential use as biofertilizer to promote the growth of mangrove-tree seedlings and reduce the use of chemical NP fertilizers.